2018
DOI: 10.1007/s00068-018-0913-z
|View full text |Cite
|
Sign up to set email alerts
|

Selective nonoperative management of liver gunshot injuries

Abstract: The NOM of carefully selected patients with GLI is safe and associated with minimal morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
1
23
0
2
Order By: Relevance
“…In PT, NOM feasibility has been reported [35][36][37][45][46][47][48][49] with 50% and 85% success rate of NOM for stab wounds (SW) in anterior and posterior abdomen respectively [34,50]. Similar managing strategy can be applied to GSWs [35,45]. Necessary distinction between low-and high-energy penetrating trauma however is mandatory when deciding for OM or NOM.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In PT, NOM feasibility has been reported [35][36][37][45][46][47][48][49] with 50% and 85% success rate of NOM for stab wounds (SW) in anterior and posterior abdomen respectively [34,50]. Similar managing strategy can be applied to GSWs [35,45]. Necessary distinction between low-and high-energy penetrating trauma however is mandatory when deciding for OM or NOM.…”
Section: Diagnosismentioning
confidence: 99%
“…In abdominal GSWs, up to 25% of non-therapeutic laparotomy has been reported [51], confirming the need to have strict selection criteria for OM or NOM even in the GSW cohort. Associated head and spinal cord injuries (that preclude affordable clinical examination) and significant reduction in hemoglobin requiring > 4 units of blood transfusion in the first 8 h [34,45] have been suggested as predictive criteria of NOM failure in abdominal GSWs.…”
Section: Diagnosismentioning
confidence: 99%
“…64 Several studies have demonstrated the efficacy and positive outcomes (69-100% of cases) of NOM in penetrating hepatic injury, even for grade III-IV injuries that required angioembolization (AE). 59,[65][66][67][68][69][70][71][72] Serial abdominal exams and contrast-enhanced CT are crucial to help guide the appropriate management of these patients. 59 Hemodynamic stability, lack of peritoneal signs, and lack of significant visceral abdominal injuries are indicators for NOM.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Firearm injuries represent the sixth leading mechanism of injury managed by the Cape Town trauma system, Cape Town, South Africa (1)(2)(3)(4)(5)(6)(7)(8). The mortality rate associated with abdominal gunshot wounds (GSWs) remains high with many deaths occurring as a result of exsanguination and irreversible shock (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%